Pengembangan Metode Pembelajaran PAI: Integrasi Ceramah, Diskusi, Tanya Jawab, dan Demonstrasi - Arif Rahman Hakim; Irwan Ruswandi; Ahmad Hilman; Mahmud Mahmud; Yeti Heryati (TA'DIB: Jurnal Pendidikan Agama Islam, 2025)
This article discusses the development of teaching methods in Islamic Religious Education with a focus on four main methods: lecture, discussion, question-and-answer, and demonstration. These four methods are commonly used approaches in Islamic Religious Education learning; however, in practice, they are often applied partially, resulting in less-than-optimal effectiveness. Through a literature review, this article examines how these methods can be developed and integrated into a single adaptive, varied, and contextual learning model. The findings indicate that the lecture method is effective for delivering normative concepts, the discussion method fosters critical thinking and tolerance, the question-and-answer method enhances active participation and two-way interaction, while the demonstration method is highly suitable for teaching practical worship and religious skills. The integration of these four methods not only improves the cognitive aspects of learners but also balances the affective and psychomotor domains. Therefore, the development of the lecture, discussion, question-and-answer, and demonstration methods can serve as a relevant strategy for improving the quality of Islamic Religious Education in the modern era.